Influence of Paddy Straw of Different Particle Sizes in the Diet on Nutrient Utilisation and Enteric Methane Emissions in Murrah Buffalo Calves - Budhani, Lalit; Mohini, Madhu; Datt, Chander; Thakur, S. S. (Indian Journal of Animal Nutrition, 2018)
Fifteen Murrah male calves were divided into three groups of five each. All the animals were offered a diet consisting of paddy straw, concentrate mixture and berseem (Trifolium alexandrinum) fodder ad lib. in 50: 40: 10 ratio. Group G-I was fed with paddy straw of small particle size (0.88 cm), G-II with long particle size (2.45 cm) and G-III with unchaffed paddy straw. The feed intake was higher (P